Analysis of the quality of biobriquettes from salak skin with starch adhesive - Gloria Sirait (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
This study aims to analyze the quality of biobriquettes made from salak skin with starch adhesive. Biobriquettes are one of the alternative fuel solutions that are environmentally friendly and can reduce organic waste. The analysis method used in this study is qualitative analysis. Salak fruit produces waste in the form of salak skin which is brownish and slightly prickly, then the salak seeds have a very hard texture which is black and brown. Salak seeds have a very hard texture so they are suitable as a basic ingredient for making briquettes The research method includes:the preparation stage of raw material for salak skin, carbonization stage of salak skin, adhesive material preparation stage and biobriquette quality analysis. From the research results, it can be concluded that both biobriquette samples, namely sample A (without adhesive) and sample B (with adhesive) have met the requirements of SNI No. 01-6235-2000 concerning charcoal biobriquettes.